(untitled) (Global Journal of Management and Business Research, 2019)
Relationship Between Accounting Variables and Market Price of Shares: essential theme of this paper is to examine the information content of accounting variables relating to the market price of the shares of listed companies in Jordan. For the purpose of the analysis, four accounting variables have been selected viz., ROE, Growth rate, Interest Coverage Ratio, and Total Assets Turnover Ratio. Panel Data regression has been done to analyze the impact of the select accounting variables on the market price of the shares. Descriptive statistics have calculated to understand the characteristics of the variables used in regression analysis. In other words, indicates a difference between Market Price and Book Value. If the ratio is more than one, it elucidate that the shares are valued at a premium. On the other hand, if ratio is less than one, it a denotes that the shares are valued at a discount. There are no studies on the analysis of the information content of accounting variables in predicting the stock price movement. To fill the research gap, in the present study, analysis of the information content of accounting variables was made by using the panel data regression model.